Complete mitochondrial genome of Lutzomyia (Nyssomyia) umbratilis (Diptera: Psychodidae), the main vector of Leishmania guyanensis. (1st November 2016) - Kocher, Arthur; Gantier, Jean-Charles; Holota, Hélène; Jeziorski, Céline; Coissac, Eric; Bañuls, Anne-Laure; Girod, Romain; Gaborit, Pascal; Murienne, Jérôme
Abstract: The nearly complete mitochondrial genome of Lutzomyia umbratilis Ward & Fraiha, 1977 (Psychodidae: Phlebotominae), considered as the main vector of Leishmania guyanensis, is presented. The sequencing has been performed on an Illumina Hiseq 2500 platform, with a genome skimming strategy. The full nuclear ribosomal RNA segment was also assembled. The mitogenome of L. umbratilis was determined to be at least 15, 717 bp-long and presents an architecture found in many mitogenomes of insect (13 protein-coding genes, 22 transfer RNAs, two ribosomal RNAs, and one non-coding region also referred as the control region). The control region contains a large repeated element of c. 370 bp and a poly-AT region of unknown length. This is the first mitogenome of Psychodidae to be described.